CUSTOMER EXPERIENCE OF MULTI-SERVICE PLATFORM: THE MEDIATING ROLE BETWEEN BRAND EXTENSION STRATEGY AND BRAND IMAGE - Hermawan, Daniel; Gunawan, Theresia; Li, Zhiwen (Dinasti International Journal of Management Science, 2020)
As the pioneer in multi-service platform, GO-JEK faces tight competition from other similar type of businesses. GO-JEK extends its product through a lot of extensions to strengthen GO-JEK’s position. This research aims to analyze the impact of brand extension strategy on brand image with customer experience as the mediating role. The type of research is explanative, research method using survey with quantitative approach, and data analyze using Sobel test to determine the impact of brand extension strategy on brand image with customer experience as the mediating role. Based on data analyze result from 378 samples, brand extension strategy gives significant contribution to customer experience, customer experience gives significant contribution to brand image, brand extension strategy gives significant contribution to brand image, and brand extension strategy through customer experience give significant contribution to brand image. So there’s mediating role of customer experience to mediating the impact of brand extension strategy on brand image of GO-JEK in Bandung.